2005
DOI: 10.3346/jkms.2005.20.6.1079
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Uterine Rupture in the First Trimester: A Case Report

Abstract: Uterine rupture is one of the most feared obstetric complications affecting the pregnant woman and fetus. Most of the cases have various risk factors and mainly occur during the second or third trimester. However, spontaneous uterine rupture during the first trimester is extremely rare. We experienced a case of spontaneous uterine rupture in a 36-yr-old multiparous woman without definite risk factors. The initial impression was a hemoperitoneum of an unknown origin with normal early pregnancy. Intensive surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 9 publications
(13 reference statements)
0
34
0
1
Order By: Relevance
“…dus and repaired with one layer of suture after suction of gestational material. 7 Singh et al and Kahyaoglu et al previously reported uterine rupture cases with uterine anomaly in the first trimester. 8,9 Tola presented a case at 12 weeks of gestation with bicornuate uterus.…”
Section: Discussionmentioning
confidence: 99%
“…dus and repaired with one layer of suture after suction of gestational material. 7 Singh et al and Kahyaoglu et al previously reported uterine rupture cases with uterine anomaly in the first trimester. 8,9 Tola presented a case at 12 weeks of gestation with bicornuate uterus.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeries of upper segment of uterus like Hysterotomy, classical Caesarean section, myomectomy, previously repaired uterine rupture, metroplasty, and LSCS with inverted T shaped extension are more prone to uterine rupture early during pregnancy and at term. 3 Risk factors for rupture uterus are multiparity, uterotonic drugs, placenta percreta, intrauterine manipulations such as internal podalic version, malpresentation, malposition, multiple pregnancy and perforation of uterus during MTP. Previous surgery on uterus like Caesarean Section, myomectomy, utriculoplasty is a strong risk factor for rupture uterus.…”
Section: Discussionmentioning
confidence: 99%
“…2 It is commonly diagnosed with a history of previous scar on uterus, but rupture of uterus in a primigravida with no risk factors is extremely rare. 3 We report a case of uterine rupture in primigravida who had no history of uterine surgeries. Underlying factor could not be identified.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of treatment, uterine defect was repaired in 50% of the cases (4 cases) and hysterectomy was performed in 3 cases. Maternal outcome was fortunately good in all cases (5,(10)(11)(12)(15)(16)(17) (Table 1). Our patient was the fourth case affected at gestational age of 12 weeks or less.…”
Section: Introductionmentioning
confidence: 96%